2006
DOI: 10.1160/th05-11-0772
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and systemic inflammation in persons with echolucent carotid plaques

Abstract: Echolucent carotid plaques are associated with high risk for future ischemic cerebrovascular events independent of the degree of stenosis. Elevated levels of markers of systemic inflammation and endothelial dysfunction are predictors for future myocardial infarction and stroke. The present study was undertaken to investigate the relations between plaque morphology, endothelial dysfunction assessed by tissue-plasminogen activator antigen (t-PA ag) and vonWillebrand factor (vWF), and systemic inflammation in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…In our study, patients with large-artery atherosclerotic infarcts did not exhibit peripheral ED to the same extent as other stroke subtypes compared with controls. This contradicts previous studies [35,36] and needs further investigations. All subgroup analyses should, however, be viewed with some caution due to small patient cohorts in each subgroup.…”
Section: Discussioncontrasting
confidence: 93%
“…In our study, patients with large-artery atherosclerotic infarcts did not exhibit peripheral ED to the same extent as other stroke subtypes compared with controls. This contradicts previous studies [35,36] and needs further investigations. All subgroup analyses should, however, be viewed with some caution due to small patient cohorts in each subgroup.…”
Section: Discussioncontrasting
confidence: 93%
“…On the one hand, a high VWF level at admission is indicated as a marker of severe IS; on the other hand, VWF level is influenced by a variety of other variables (e.g. ABO blood group [38][41], existence and composition of carotid plaques [15], [16]) which complicates its interpretation. Only recently, it has been shown that extracellular sodium levels within the high physiological range can raise VWF levels thereby increasing the risk of pathological thrombosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the relationship of VWF levels to other parameters, such as genetic polymorphisms [13] and demographic features [14], is not well understood. Additionally, only limited data exist on the regulation of VWF in patients with chronic cerebrovascular disease (CCD) [15][17].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased brachial FMD and decreased cerebrovascular reactivity to L-A are present in stroke patients [19,77,78,79] and in patients with carotid stenosis [57, 80, 81]. L-A reactivity is impaired in the stenotic side of patients with severe unilateral internal carotid stenosis and normalizes 3 months after endarterectomy [80].…”
Section: Endothelial Dysfunction In Strokementioning
confidence: 99%
“…L-A reactivity is impaired in the stenotic side of patients with severe unilateral internal carotid stenosis and normalizes 3 months after endarterectomy [80]. Moreover, the presence of carotid stenosis is related to higher plasma t-PA and vWF concentrations, and persons with echolucent carotid plaques have a higher degree of systemic inflammation [81]. Impaired FMD seems to be especially important in lacunar infarction and may be considered an independent predictor for this stroke subtype [19].…”
Section: Endothelial Dysfunction In Strokementioning
confidence: 99%